Socio-Economic Dimension of Human Potential of World Countries in the Digital Space of the Labor Market - Olena O. Vasyl’yeva; Andrii V. Sokolov; Marharyta O. Lisnichenko; Olena Ye. Halan; Tamila V. Butenko (Qubahan Academic Journal)
The article examines the special socio-economic conditions of human potential, which forms and expands the flow of labor in the international digital labor market. The concept of the socio-economic dimension of human potential based on the unity of its components is presented. The hypothesis of effective use of human potential at all levels of its formation is justified by relevant HRM technologies that align the labor market situation with the rate of modernization of business, state policy, and social institutions, as well as the new nature of the digital economy's growth. It is also demonstrated that, in the context of the informational transformation of the labor market, the concentration, implementation, and effective socio-economic dimension of human potential form a consistent state policy, which is strengthened by the possibilities of territorial decentralization and is aimed at overcoming disparities in the use of human resources, reducing the gap between potential and existing social-economic level of development of the countries of the world. The authors also provide the sectoral structure of employment in Ukraine and the average annual rate of growth of the indicator level in the leading countries with a digital direction of labor market development, as well as comparative socio-economic measurement and forecasting of Germany's effective use of human potential, subject to the expansion of labor inflows and the improvement of the working capacity of active human resources.